1994
DOI: 10.1111/j.1365-2362.1994.tb01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable patterns of atrial natriuretic peptide secretion in man

Abstract: Peripheral circulating levels of atrial natriuretic peptide may exhibit short-term variation compatible with a pulsatile pattern of secretion. We obtained samples every 2 min for 90 min from the antecubital vein of 16 patients with chronic cardiac failure and 13 controls. Overall levels were higher in the patients (median and quartiles 230 (125,325) vs. 26 (16,48) ng l-1; P < 0.001). In both groups there was considerable variability, with 10 (2-12) peaks, 9 (7-15) troughs (both defined as > 2 SD from the mean)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 32 publications
6
24
2
Order By: Relevance
“…Whereas plasma concentrations of the C-terminal peptides BNP and ANP are low and fluctuate rapidly, 26 half-life times of the N-terminal peptides NT-proANP and NT-proBNP are considerably longer, 27,28 resulting in at least 5-to 15-timesgreater plasma levels. The N-terminal peptides may therefore be even more sensitive for the detection of left ventricular dysfunction in critical care settings because they are less influenced by the conditions under which the blood sample is taken.…”
Section: Discussion Natriuretic Peptides and Cardiac Dysfunction In Smentioning
confidence: 99%
“…Whereas plasma concentrations of the C-terminal peptides BNP and ANP are low and fluctuate rapidly, 26 half-life times of the N-terminal peptides NT-proANP and NT-proBNP are considerably longer, 27,28 resulting in at least 5-to 15-timesgreater plasma levels. The N-terminal peptides may therefore be even more sensitive for the detection of left ventricular dysfunction in critical care settings because they are less influenced by the conditions under which the blood sample is taken.…”
Section: Discussion Natriuretic Peptides and Cardiac Dysfunction In Smentioning
confidence: 99%
“…During exercise in such patients the relative increase in ANP levels is less than in normal subjects [35]. This is probably not due to a ceiling on ANP release, as intermittent very high levels may still be recorded [24]. It has been suggested that the major circulating form in patients is the antiparallel dimer of alpha ANP, termed P-ANP, which has reduced biological activity [36], but recent work in our laboratories suggest that this may not be the case.…”
Section: Cardiovascular Eflectsmentioning
confidence: 54%
“…Recent studies have suggested that there may be short-term variations in the release of ANP independent of heart rate or right atrial pressure, which can give rise to peak levels about every 10-12min [23,24]. The significance of these observations is, at present, unclear, but it does mean that isolated values should be interpreted with caution.…”
Section: Mechanism Of Releasementioning
confidence: 71%
“…Radioimmunoassay and Immunocytochemical Studies of Peptides in the Rat Heart Cardiology 1998;90:95-100 97 er related analogues was also used [18]. The primary antisera were applied at their optimal working dilution and incubated for 20 h at 4°C in a sealed moist container.…”
Section: Wax Processed Methodsmentioning
confidence: 99%
“…The extracts were centrifuged at 1,700 g for 30 min at 4°C, the supernatants decanted, air-dried and stored at -20°C prior to radioimmunoassay. Radioimmunoassay of hANP and NPY were performed using antibody to ·-hANP, and C-terminal NPY hexapeptide analogue and methology established [18][19][20][21]. The sensitivity of the assays were 1.2 fmol ANP/assay tube and 20 ng/l for NPY.…”
Section: Radioimmunoassaymentioning
confidence: 99%